2013
DOI: 10.1103/physreva.88.013602
|View full text |Cite
|
Sign up to set email alerts
|

Quantum phase transition in a three-level atom-molecule system

Abstract: We adopt a three-level bosonic model to investigate the quantum phase transition in an ultracold atom-molecule conversion system which includes one atomic mode and two molecular modes. Through thoroughly exploring the properties of energy level structure, fidelity, and adiabatical geometric phase, we confirm that the system exists a second-order phase transition from an atommolecule mixture phase to a pure molecule phase. We give the explicit expression of the critical point and obtain two scaling laws to char… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…zν = 1 2 is the critical exponent, which is usually universal due to its independence of most of microscopic details of the Hamiltonian Ĥ (q). Relation ( 6) is verified by the results illustrated in figure 4(c) for different c. We emphasize that the above characteristic scaling laws and corresponding critical exponents for the QPT are quite different from those obtained for both two-and three-level bosonic atom-bosonic molecule conversion systems in previous works [23,42]. This implies that our QPT for the modified spinboson model and the QPTs for previous two-or three-level bosonic model belong to different universality classes.…”
Section: Characteristic Scaling Lawssupporting
confidence: 64%
See 2 more Smart Citations
“…zν = 1 2 is the critical exponent, which is usually universal due to its independence of most of microscopic details of the Hamiltonian Ĥ (q). Relation ( 6) is verified by the results illustrated in figure 4(c) for different c. We emphasize that the above characteristic scaling laws and corresponding critical exponents for the QPT are quite different from those obtained for both two-and three-level bosonic atom-bosonic molecule conversion systems in previous works [23,42]. This implies that our QPT for the modified spinboson model and the QPTs for previous two-or three-level bosonic model belong to different universality classes.…”
Section: Characteristic Scaling Lawssupporting
confidence: 64%
“…Before concluding, by comparing the bosonic atom-molecule conversion model [23,41,42] with our modified spin-boson model, we have three remarks. First, it is found that the critical point for the QPT in the former system depends on the molecular interaction while that in the latter system does not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments, the atom-molecule oscillations using either identical bosons in a BEC [8,14] or confined pairs in a deep optical lattice potential [12] can be well described by a twolevel model. This two-level boson system can be a paradigm model used to demonstrate quantum dynamics [15] and quantum phase transition (QPT) [16][17][18]. Recently, the process of production of ultracold molecules from ultracold atoms using a sinusoidally oscillating magnetic-field modulation [19] has been discussed, and this method has been successfully applied to produce molecules with high efficiency [11].…”
Section: Introductionmentioning
confidence: 99%